Introduction [in Food systems transformation in Kenya: Lessons from the past and policy options for the future] - Breisinger, Clemens; Keenan, Michael; Mbuthia, Juneweenex; Njuki, Jemimah (International Food Policy Research Institute, 2023)
The whole world has experienced a series of global and local crises since 2019, and Kenya has been no exception. Before the COVID-19 pandemic and the Russian invasion of Ukraine, poverty and food poverty rates in the country had been declining steadily, falling from 52.3 percent to 36.1 percent and from 38.3 percent to 26.7 percent, respectively, between 1997 and 2016 (KNBS 2007, 2018). Income inequality also declined in the period from 1994 to 2015/16 (KNBS 2020). Estimates suggest that, since then, progress in poverty reduction has reversed, as a result of COVID-19 (Nafula et al. 2020), and that the impacts of the Ukraine and global crises have further increased poverty levels and the number of people unable to afford a healthy diet (Breisinger et al. 2022). In addition, ongoing droughts in the arid and semiarid areas of Kenya meant that an estimated 3.5 million people were in need of assistance in May 2022 (UNICEF 2022).